Fecal Microbiota Transplant Mitigates Adverse Outcomes Seen in Patients Colonized With Multidrug-Resistant Organisms Undergoing Allogeneic Hematopoietic Cell Transplantation - Innes, Andrew J.; Mullish, Benjamin H.; Ghani, Rohma; Szydlo, Richard M.; Apperley, Jane F.; Olavarria, Eduardo; Palanicawandar, Renuka; Kanfer, Edward J.; Milojkovic, Dragana; McDonald, Julie A. K.; Brannigan, Eimear T.; Thursz, Mark R.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The gut microbiome can be adversely affected by chemotherapy and antibiotics prior to hematopoietic cell transplantation (HCT). This affects graft success and increases susceptibility to multidrug-resistant organism (MDRO) colonization and infection. We performed an initial retrospective analysis of our use of fecal microbiota transplantation (FMT) from healthy donors as therapy for MDRO-colonized patients with hematological malignancy. FMT was performed on eight MDRO-colonized patients pre-HCT (FMT-MDRO group), and outcomes compared with 11 MDRO colonized HCT patients from the same period. At 12 months, survival was significantly higher in the FMT-MDRO group (70% versus 36% p = 0.044). Post-HCT, fewer FMT-MDRO patients required intensive care (0% versus 46%, P = 0.045) or experienced fever (0.29 versus 0.11 days, P = 0.027). Intestinal MDRO decolonization occurred in 25% of FMT-MDRO patients versus 11% non-FMT MDRO patients. Despite the significant difference and statistically comparable patient/transplant characteristics, as the sample size was small, a matched-pair analysis to non-MDRO colonized control cohorts (2:1 matching) was performed. At 12 months, the MDRO group who did not have an FMT had significantly lower survival (36.4% versus 61.9% respectively, p=0.012), and higher non relapse mortality (NRM; 60.2% versus 16.7% respectively, p=0.009) than their paired non-colonized cohort. There was no difference in survival (70% versus 43.4%, p=0.14) or NRM (12.5% versus 31.2% respectively, p=0.24) between the FMT-MDRO group and their paired cohort. Negative outcomes, including mortality associated with MDRO colonization, may be ameliorated by pre-HCT FMT, despite lack of intestinal decolonization. Further work is needed to explore the observed benefit.